Approaches to Understanding Peaceful Conduct among Young Students: a Positive Psychology Perspective - Ferrel Ortega, Fernando Robert (Pensando Psicología, 2015)
Purpose: To reflect and postulate concepts, categories and strategies for developing peaceful conduct, particularly among children and young people, both in education and research, from the perspective of positive psychology, in terms of healthy conduct that will promote a new culture of peace. Topic: The importance of the social learning theory of Albert Bandura and recent contributions by Richard Tremblay on the learning of violent and peaceful conduct in early childhood; also reflections on the ability to teach prosocial peaceful conduct from a critical posture, which questions social approval of violence by the status quo. Development: The violent conduct of one or more individuals, aimed at hurting other people, is a constant concern in the social and human sciences, as well as for individuals, society and the State. Until now, research into the causal factors and control and management of their consequences has aimed at sanctioning, punishing and impeding violent conduct, without trying to discover and mold that conduct that human beings need for their survival, in healthy coexistence, here denominated as “peaceful conduct”, or behavior that is the opposite of violent conduct. Conclusions: Learning peaceful conduct would result in healthy social coexistence along with healthy, human and supportive development characterized by dialogue, thus leading individuals to practice healthy and happy interpersonal and social relationships, as resources that give meaning to human life in all of its activities.